2022
DOI: 10.1007/s12671-022-01909-4
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Group–Based Mindfulness Intervention for Autistic Adults: a Feasibility Study

Abstract: Objectives Although mindfulness-based interventions have been shown to be helpful in reducing psychological distress in autistic adults, limited research has explored virtual delivery in the autism community. We designed an adapted virtual group-based mindfulness intervention, based on input from autistic adults, and evaluated its feasibility in terms of demand, acceptability, implementation, practicality, adaptation, and limited efficacy testing. Methods Informed by an online needs assessment survey of 77 aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 48 publications
2
29
1
Order By: Relevance
“…In contrast to our previous work examining the impact of mindfulness on a larger cohort of autistic adults, 24 preliminary quantitative results from the current study did not reach statistical significance. While quantitative results showed no improvements, qualitative feedback suggested that the autistic women were satisfied and benefited from the group.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to our previous work examining the impact of mindfulness on a larger cohort of autistic adults, 24 preliminary quantitative results from the current study did not reach statistical significance. While quantitative results showed no improvements, qualitative feedback suggested that the autistic women were satisfied and benefited from the group.…”
Section: Discussioncontrasting
confidence: 99%
“…Findings from this study showed that most of the participants appreciated that the program was delivered online. This was also found in the Lunsky et al 24 study, in which participants described that the online nature of the program addressed barriers such as stresses associated with in-person communication and transportation. In addition, the online nature of the program allowed participants to meet autistic people from different provinces.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations